Book Frontiers Reconstructing Readers and Reading in a Nineteenth Century Eastern Cape Missionary Journal - Clarke, Russell Paul (My University, 2006)
This study is a historical analysis of readers and the practices of reading in the late nineteenth century Eastern Cape, with particular focus on the Lovedale Institution. Well known as the progenitor of an African elite, the Lovedale mission institution, school and Press have been well-documented and studied, as has the Eastern Cape frontier – but the role of books and reading in their social and material practice has seldom been examined in very close detail in relation to this imagined textual community. A close examination of the contemporary evangelical journal, The Christian Express, reveals much in terms of what was being read, and how reviews and secondary matter on texts that were in circulation may have influenced conceptions of what books and literacy meant to the people reading the journal. These ideas have been traced through advertisements, reviews, columns and letters in order to understand the ways in which the journal portrayed books as material and intellectual objects. Delving deeper than the materiality of the book in an empirical world, however, this study seeks to analyse how books and readers were both constructed and represented, and involves an attempt (although admittedly a highly theoretical undertaking) to reconstruct the various reading strategies employed by readers on the frontier of race, class, and nation.
Faculty of Humanities School of Language and Literature 9807000g russelle@webmail.co.za
Keywords: Readers; Reading; Eastern Cape; Lovedale; Alice